Oscillatory behaviour in Type IA FBG: Ruling out chemical complexity - Simpson, George D.; Kalli, Kyriacos; Canning, John; Lacraz, Amédéé (My University, 2015)
Type IA FBG are regenerated gratings that appear in hydrogenated germanosilicate fibre of all types during prolonged UV exposure. The gratings are characterised by a large Bragg wavelength shift and a concomitant increase in the mean fibre core index. Modulated index changes are complex by comparison and significantly weaker, often characterised by oscillatory growth behaviour. Low thermal stability of Type IA gratings suggests a possible chemical role similar to thermally processed optical fibres where autocatalysis has been observed. We show that GeOH and SiOH formation are not out-of-phase and follow each other, with no evidence of autocatalysis, ruling out a chemical origin.
Keywords: Absorption spectra; Fibre bragg gratings; Hydrogenation; Optical fibre sensors